Світове виробництво та ринкові позиції плодово-ягідної продукції на міжнародному ринку - Колокольчикова, Ірина Володимирівна; Kolokolchykova, Iryna (Київ : МУБІП, 2019)
UA: У статті досліджено тенденції світового виробництва та ринкові позиції плодово-ягідної продукції на міжнародному ринку. На сучасному етапі розвитку споживання плодово-ягідної продукції у світі має тенденцію до зростання. зміни вподобань споживачів, стилю життя та культура споживання фруктів вимагають від виробників та їхніх країн гнучкість і корегування стратегічних програм розвитку цієї галузі. країни світу виступають як окремі сегменти і мають специфічне пропонування та відповідне позиціювання на світовому ринку плодів та ягід. Зокрема, встановлено, що станом на 2017 р. На першому місті стоїть виробництво кавунів, друге та третє місця – виробництво бананів і яблук. Урожайність зерняткових плодових культур практично вдвічі перевищує аналогічний показник по кісточковим, субтропічні культури мають найвищі показники продуктивності. За побудованим рейтингом вартості експортно-імпортних операцій найбільші грошові потоки проходять по горіхах, ягодах та цитрусових, як по вартості, так і в структурі здійснених операцій. EN: The article investigates the trends of world production and market position of fruit products in the international market. At the present stage of development of consumption of fruit products in the world tends to grow. changes in consumer preferences, lifestyle and culture of fruit consumption require producers and their countries to be flexible and adjust strategic directions in the development of this industry. The countries of the world act as separate segments and have specific offers and corresponding positioning in the world market of fruits and berries. Therefore, the purpose of the study is to study the results of production and marketing activities of enterprises of individual countries in the world production and the international market of fruit and berry products at the present stage in the context of the dynamics of changes in product supply and geographical structure. In order to generalize the trends in the development of fruit and nut production in the world, a monographic method was used to study the indicators of the production of individual products of the industry, the yield of perennial plantations. The method of systematic approach makes it possible to determine priorities in the development of the industry. Statistical methods made it possible to obtain estimates of the productivity of popular fruit production, as well as to determine the structure of exports and imports in the reporting year. Tables and graphs are constructed on the basis of statistical information. In particular, it was established that as of 2017. in the first place in the production of the industry is the berry – watermelon, the second and third place in the production of bananas and apples. The yield of pommes crops is almost twice higher than that of stone crops, subtropical crops have high performance. According to the rating of the value of export – import operations, the largest cash flows are for nuts, berries and citrus fruits both in monetary terms and in the structure of operations. The result of the study of the world market for the production of fruits and berries, as well as the scale of exports and imports is that the world market is aimed at the production of berries and citrus fruits, and in the structure of exports and imports dominate in addition to the above products - nuts. They have a special place in this industry.
World production and market position of fruit and berry products on the international market
Keywords: світове виробництво; плодово-ягідна продукція; експорт; імпорт; міжнародний ринок; world production; fruit and berry production; export; import; international market